KNOWLEDGE, PRACTICE TOWARD COVID-19 PREVENTION AMONG PEOPLE LIVING IN TAN PHU DISTRICT, HO CHI MINH CITY 2020 (Vietnam Journal of Community Medicine, 2021)
This study aims to assess the accessibility of information ressources and knowledge, practice toward COVID-19 prevention among people living in Tan Phu district, at Ho Chi Minh City. Cross-sectional study was performed from June 2020 and used two-stage random sampling. Data was collected by self-management questionnaire. Television and the Internet are most commonly accessed. Many people underrate COVID-19 infected risk in healthy people, children, and young people, and misperception that only wearing masks properly does not need to use other precautions, limiting hand washing practices and cleaning surfaces. Health education and communication programs need to pay more attention to the limitations of knowledge and practice, and choose appropriate communication channels to improve the effectiveness of COVID-19 prevention and control
Keywords: COVID-19, knowledge, practice